Time trend of measles burden on children and adolescents in BRICS-plus countries from 1990 to 2021 and prediction to 2032 - Yuan, Hongxia; Yan, Bingju; Chong, Yiran; Wang, Le; Jiang, Yong (Frontiers in Microbiology, 2025)
BackgroundMeasles remains a major disease burden on children and adolescents in BRICS-plus countries (Brazil, Russia, India, China, South Africa, and five others) despite vaccine efficacy. This study aims to clarify the temporal trend of measles burden and forecast the trend in 2032.MethodsData from the Global Burden of Disease (GBD) 2021 were utilized to analyze the prevalence, incidence, mortality, and disability-adjusted life years (DALYs) of measles in BRICS-plus countries. In addition, the association between the social development index (SDI) and measles-related indicators of children and adolescents in BRICS-plus countries was analyzed. Joinpoint regression was performed to identify temporal trends, while the age-period-cohort model was used to assess demographic effects. The Bayesian Age-Period-Cohort (BAPC) and Autoregressive Integrated Moving Average (ARIMA) models were utilized to project indicators to 2032.ResultsFrom 1990 to 2021, the global prevalence of measles dropped by 92% (with an average annual decline of 6.80%), and the average annual decline rates for incidence, mortality, and DALYs were 6.80, 8.02, and 8.02%, respectively. Saudi Arabia had a 100% reduction in prevalence (with an average annual decrease of 15.20%), Ethiopia had the highest DALYs (124542.02), and Russia had the lowest DALYs (1.74). SDI was negatively linked to the measles prevalence (R = −0.703, p < 0.001), and an increase in SDI significantly reduced the burden of measles. The prevalence of measles was highest among children under 5 years old and slightly higher in males than in females. Joinpoint analysis indicated that the global burden of measles declined, but its mortality in China sharply increased from 2019 to 2021 (APC = 191.88). The BAPC model predicted that by 2032, the global burden of measles will continue to decline, India will still have the highest prevalence (130.96), Russia may have no new cases, and Brazil and South Africa will have controllable local risks. ARIMA models showed similar trends.ConclusionThe declining burden of measles in BRICS-plus countries is correlated with SDI improvement, but low-income countries such as Ethiopia still face a high burden of measles. Children under 5 years and regions with low vaccination rates require prioritized interventions. The burden of measles will continue to decrease in the next decade, and increasing vaccination coverage in high-burden countries will help achieve the goal of measles elimination.